2018
DOI: 10.1590/abd1806-4841.20187014
|View full text |Cite
|
Sign up to set email alerts
|

A case series pilot study on the combination of 5-aminolevulinic acid and photodynamic therapy (ALA-PDT) for treatment of vitiligo

Abstract: BackgroundTo study the effective therapeutic concentration, drug application duration, irradiation duration and irradiation dosage of 5-aminolevulinic acid photodynamic therapy (ALA-PDT) for treating vitiligo and observe its clinical efficacy.ObjectiveTo assess the clinical efficacy of ALA-PDT for treating vitiligo.MethodsALA with different drug concentrations, drug application durations, irradiation durations and irradiation dosages were adopted to treat skin lesions caused by vitiligo to determine the effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 17 publications
(19 reference statements)
0
9
0
Order By: Relevance
“…In a preliminary analysis of photodynamic therapy with 5-aminolevulinic acid (ALA) in treating vitiligo, 3 patients were treated with ALA at a drug concentration of 1.5%, applied for 3 hours before irradiation with UV-A at 80mw/cm2 for 20 min and was effective in treating vitiligo. The treatment was associated with mild pain and burning sensation, but no other adverse reaction was noted [106].…”
Section: Photodymanic Therapymentioning
confidence: 87%
“…In a preliminary analysis of photodynamic therapy with 5-aminolevulinic acid (ALA) in treating vitiligo, 3 patients were treated with ALA at a drug concentration of 1.5%, applied for 3 hours before irradiation with UV-A at 80mw/cm2 for 20 min and was effective in treating vitiligo. The treatment was associated with mild pain and burning sensation, but no other adverse reaction was noted [106].…”
Section: Photodymanic Therapymentioning
confidence: 87%
“…On the other hand, in a number of studies, the effectiveness of PDT in the treatment of vitiligo has been demonstrated. Zhang et al treated vitiligo lesions with 1.5% 5-ALA, followed by 80 mw/cm 2 red light irradiation and found that 5-ALA-PDT effectively repigments vitiligo patches to some extent [ 104 ]. Similarly, Serrano and colleagues reported some degree of repigmentation in vitiligo lesions treated with PDT [ 105 ].…”
Section: Photodynamic Therapy Applicationsmentioning
confidence: 99%
“…Mono- and di-selenide-containing polymers are insoluble in aqueous solutions and are used in the fabrication of amphiphilic block copolymers. Telluride is less toxic and more sensitive to ROS than selenide and sulfide due to its lower electronegativity which make it a suitable composition in design and synthesis of copolymers and polymers for drug delivery systems and ROS-responsive prodrug preparation [ 104 ]. The prodrugs consisted of three domains, a ROS acceptor that can be sensitive to ROS, an effector that is the native drug part, and a linker between the ROS acceptor and the effector.…”
Section: Ros-responsive Materials Along With Pdt For Skin Wound Healingmentioning
confidence: 99%
See 1 more Smart Citation
“…These observations may partially explain why PDT did not achieve brilliant results in treatment of vitiligo in pediatric patients. Zhang et al (2018 ) conducted a study to determine the effective PS concentration, PS application duration, irradiation duration, and irradiation dosage for the treatment of vitiligo. They selected ALA concentration of 1.5%, PS application duration of 3 h, irradiation duration of 20 min, and irradiation dosage of 80 mw/cm 2 as the better parameters for treating their patients.…”
Section: Miscellaneamentioning
confidence: 99%